A comparison study of leisure activities between the arts and sciences students in University of Malaya / Chin Kek Way - Chin , Kek Way (1985)
This case study is a comparison study of leisure activities between the arts and sciences students in University of Malaya. The aim of the study is to find out the difference in the type of leisure activity pursued by the arts and Sciences students. In order to provide a clear and systematical picture, the writer has arranged this study into various chapters. Chapter I gives a general introduction of the objective and significance of this study. It also discusses the research methodology used and the problems encountered during the fieldwork. Chapter II present the meaning and use of leisure as well as its concepts, functions and types of leisure activity. Chapter III deals the factors to be considered in determining the type of leisure activity. It also touches on various aspects of education which affect the students leisure. Chapter IV given a deeper understanding on the various types of leisure activities pursued by the arts and science students. Chapter V attempts to describe the views and satisfaction of leisure from the students point of view. Finally, the conclusion analysis the findings and implication of the study. The writer concludes by putting forward suggestions and recommendations.